Using gold nanoparticles with high energy gamma photons (12MeV)to treat brain cancer - Jalaukhan , Ali H. A.; Khadayeir, Abdulhussain A. (University of Thi-Qar Journal, 2019)
This paper deals with one of the interesting topic in medical application where Gold nanoparticles (GNPs) are good choice due to characterize ability of synthesis as colloidal solution as well as did not interact with healthy tissue, less toxicity, ease of detection and thermal stability. The brain cancer can be treatment by high energy photons of gamma ray about (12 MeV) and gold nanoparticles while preserving the brain and prevents the risk of recurrence of brain cancer. This occur in a minimum dose given for patient i.e. enhancing the radiotherapy that is used in brain cancer treatment by depending on pair production phenomena. Our results showed that GNPs have significantly enhancing the radiotherapy for brain cancer treatment with high energy of gamma photons (12MeV).